Statins did not reduce the frequency of exacerbations in individuals with COPD and cardiovascular comorbidities in the COSYCONET cohort - Frantzi, Nikoleta; Nguyen, Xuan Phuc; Herr, C.; Alter, P.; Söhler, S.; Soriano, Daniel; Watz, H.; Waschki, B.; Trinkmann, Frederik; Eichenlaub, M.; Trudzinski, Franziska; Michels-Zetsche, Julia D.; et al. (Respiratory research, 2024)
The evidence regarding effects of statins on exacerbation risk in COPD remains controversial. Previous studies often excluded patients with cardiovascular comorbidities despite their high prevalence in COPD and role for exacerbations. Based on the cardioprotective properties of statins, we hypothesised that statins may reduce the risk of exacerbations especially in patients with cardiovascular comorbidities.
Gesehen am 25.11.2024